Peran Bauran Pemasaran Dalam Meningkatkan Citra Lembaga Pendidikan di Kabupaten Ponorogo - Syifani Nata Sabila; Abdul Kholiq (Edumanagerial, 2023)
The marketing mix strategy is a tool for marketers consisting of various marketing elements that are implemented to achieve the goals of educational institutions. One of the goals to be achieved is to improve the image of the institution. The image of an educational institution is a picture that educational institutions have and affects the views of the community. This study aims to describe and analyze (1) the application of the marketing mix strategy in educational institutions (2) Supporting factors and inhibiting factors of the marketing mix strategy in educational institutions (3) The results of the application of the marketing mix strategy in educational institutions This study uses a descriptive qualitative approach with data collection techniques using interviews, observation and documentation. Data analysis techniques are carried out with four stages, namely data collection, data reduction, data presentation and conclusion drawing. Checking the validity of the data using the extension of participation, persistence of observation and data triangulation. The results showed that: (1) the implementation of marketing strategies is carried out through products, prices, places, promotions, human resources, physical evidence and processes (2) supporting factors consist of qualified educators, strategic locations, excellent programs, affordable financing and community trust. While the inhibiting factor is the number of competitors from other institutions so that competition occurs (3) the results of implementing the marketing mix strategy can improve the image of the institution and influence and encourage people's decisions to send their children to an educational institution.